INVESTMENT IDEAS IN A VOLATILE ENVIRONMENT - A STUDY CASE FOR THE 2012 SOCIETY - VERONICA ADRIANA POPESCU; GHEORGHE N. POPESCU; CRISTINA RALUCA POPESCU (Challenges of the Knowledge Society)
The year 2011 has proven to be a highly volatile year, especially if we take into account the Eurozone crisis. Even so, the year 2011 has proved to be a year in which great opportunities were created, as well. Our article “Investment Ideas in a Volatile Environment - A Study Case for the 2012 Society” starts by presenting both the strong and the weak points of the year 2011, in terms of assets markets and net results, continuing with the general outlook of the year 2012 and putting a strong emphasis on the investment ideas for 2012. In our study we are going to describe the opportunities that exist in the year 2012, providing answers to questions such as: what equities should investors focus on, what changes can be predicted in terms of foreign exchange market, what will the evolution of the commodities be like, how will the evolution of different types of currencies look like.